2013
DOI: 10.1063/1.4816465
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser melting of La(Fe,Co,Si)13 geometries for magnetic refrigeration

Abstract: Articles you may be interested inEnhanced mechanical properties and large magnetocaloric effects in bonded La(Fe, Si)13-based magnetic refrigeration materials Appl. Phys. Lett. 104, 062407 (2014); 10.1063/1.4865236 Refrigerant capacity and direct measurements of the magnetocaloric effect on LaFe 11.2 Co 0.7 Si 1.1 C x materials J. Appl. Phys. 107, 09A933 (2010); 10.1063/1.3349372 The study on the microstructure and the magnetocaloric effects in LaFe 10.8 Co 0.7 Si 1.5 C 0.2 compound at different annealing time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(64 citation statements)
references
References 23 publications
(55 reference statements)
0
57
0
3
Order By: Relevance
“…Future magnet products and devices may be used in conditions which are not compatible with current magnet technology, such as smaller dimensions, in more complex shapes, higher integrated applications and extreme environmental/chemical conditions. On the micro/macroscale, modern additive manufacturing processes, such as 3D printing, allow, in principle, novel magnet designs [182,183], but at this stage lack a detailed understanding of the correlation of the fabrication process and materials properties, as well as the validation of useful magnetic properties. …”
Section: Materials Science Tu Darmstadtmentioning
confidence: 99%
“…Future magnet products and devices may be used in conditions which are not compatible with current magnet technology, such as smaller dimensions, in more complex shapes, higher integrated applications and extreme environmental/chemical conditions. On the micro/macroscale, modern additive manufacturing processes, such as 3D printing, allow, in principle, novel magnet designs [182,183], but at this stage lack a detailed understanding of the correlation of the fabrication process and materials properties, as well as the validation of useful magnetic properties. …”
Section: Materials Science Tu Darmstadtmentioning
confidence: 99%
“…It also revealed a problem of structure collapsing during sintering. Moore et al [9] used selective laser melting technology to fabricate a wavy-channel block and an array of fin-shaped rods. The minimum channel diameter was around 0.800 mm and a corrosion problem existed.…”
Section: Micro-channel Matrixmentioning
confidence: 99%
“…The micro-channel matrix for MCR application, which consists of numerous micro channels opened through a monolithic block, has been presented in a few of papers [8,9]. showed that the parallel plate and micro-channel matrices were preferable concerning a balance between heat transfer and pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Moore et al [136] proposed a selective laser melting (SLM) method for the production of a more sophisticated AMR geometry (compared to most widely applied, packed-bed and parallel-plate geometries). SLM is a rapid prototyping technique to form a variety of three-dimensional shapes.…”
Section: Fabrication Of Powder-based (Sintered) Amrsmentioning
confidence: 99%